THE EFFECT OF WATER TREATMENT STAGES IN AL-WATHBA WATER TREATMENT PLANT ON THE BACTERIAL GROWTH (APPLIED STUDY) - Al-Hashimi, Mohammed Ali I.; Mahdi, Ayat Hussein; Kadhim, Rana Jawad (European Scientific Journal, ESJ, 2013)
The aim of this research is to study the biological pollution in Al-Wathba water treatment plant stages (new extension) by taking water samples from the river, sedimentation tank, sand filter, pressure filter, and from three residential areas (Al-Atebaa neighborhood, Al-Amen neighborhood, Al-Shorja), with examining the bacterial growth, temperature, pH and turbidity in each stage. Weekly samples have been taken for the period from January 2011 to May 2011 by studying the bacterial existence using total plate count (TPC), also test for total and fecal coliform using presumptive and confirmed test because it’s the evidence for the bacterial pollution. There was high percent of pollution in the sedimentation tank and in less amount in sand filter due to lack of the periodic cleaning. Fecal coliform reduced after the pressure filtration, small amounts of chlorine were added to the filter to reduce the bacterial growth in filter media. After chlorination removal efficiency was 99.99%. It was noticed that chlorine dose added for disinfection was so high reached to 3.5mg/l, which is dangerous especially for people near the water treatment plant.